Development Of Hydroxypropyl Cellulose-Fe-Doped Nano-Tio2 Photocatalyst: Synthesis, Characterization And Activity Test - Teh, Chao Min (2011)
Water pollution by organic pollutants is an ever increasing problem for the global concerns. Therefore, it is important to degrade these pollutants completely before they are discharged to the environment. Most of the pollutants cannot be effectively degraded by conventional techniques such as flocculation, precipitation, adsorption, membrane separation, etc. Thus, advanced oxidation processes (AOP’s) become one of the superior methods used and widely studied for the degradation these organic pollutants.